Does Hashimoto's Thyroiditis Increase the Risk of Cardiovascular Disease in Young Type 1 Diabetic Patients? - Głowinska-Olszewska, Barbara; Borysewicz-Sańczyk, Hanna; Sawicka, Beata; Klonowska, Bożenna; Charemska, Dorota; Żelazowska-Rutkowska, Beata; Bossowski, Artur (Frontiers in Endocrinology, 2020)
Background: Immunological and hormonal disorders have undoubted influence on the development of atherosclerotic process. Autoimmune diseases accompanying type 1 diabetes (T1D) may additionally accelerate atherosclerosis progression and increase the risk of cardiovascular events in the future. The influence of subclinical hypothyroidism on the cardiovascular system, in particular, has recently aroused great interest. The aim of our study was to assess intima-media thickness (cIMT) of common carotid arteries and the occurrence of classical atherosclerosis risk factors together with selected new biomarkers of cardiovascular diseases in young patients with type 1 diabetes mellitus coexisting with Hashimoto's disease (HD). Patients and Methods: The study included 50 adolescents and young adults with T1D with mean age 17.1 ± 3 years, with mean diabetes duration of 10.5 ± 3.3 years, including 20 patients with diagnosed HD: T1D and HD(+), and 30 patients with no additional diseases: T1D and HD(–). Twenty-two healthy, age-matched volunteers formed control group (C). We analyzed mean HbA1c value from all years of disease, BMI, blood pressure, lipids, new biomarkers of atherosclerosis (hsCRP, adiponectin, myeloperoxidase, NT-proBNP peptide, vitamin D), and cIMT of common carotid arteries. Results: In the group of patients with T1D and HD(+), significantly higher BMI was found: 23.3 ± 4.4 vs. 21.28 ± 2.9 in group HD(–) and 19.65 ± 2.4 kg/m2 in group C (p = 0.003), and higher waist circumference: 79 ± 10.9 vs. 75.10 ± 7.6 in group HD(–) vs. 69.0 ± 7.4 cm in group C (p < 0.001). The mean value of HbA1c was higher in group T1D and HD(+): 8.8% than in group HD(–): 8.1% (p = 0.04). Significantly higher concentration of hsCRP and lower vitamin D were observed in T1D and HD(+) in comparison to T1D and HD(–) and the control group. The IMT index in the HD(+) group was 0.46 ± 0.05 mm and was comparable to the HD(–) group but significantly higher than in healthy controls: 0.41 ± 0.03 mm (P < 0.05). Conclusions: Young patients with type 1 diabetes mellitus and with coexisting Hashimoto's thyroiditis have a higher BMI, a higher waist circumference, and a higher HbA1c value, which altogether may cause faster development of macroangiopathy in the near future. Additional risk for cardiovascular disease may result from low vitamin D and increased hsCRP concentration in this group of patients. Coexistence of Hashimoto's thyroiditis did not significantly affect the cIMT value in the studied population.